1989
DOI: 10.1161/01.str.20.4.488
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol and dimethylthiourea reduce brain infarction following middle cerebral artery occlusion in rats.

Abstract: Free radicals have been shown to play an important role in ischemia-reperfusion injury in several organ systems; however, the role of free radicals in central nervous system ischemia has been less well studied. Many potential free radical-generating systems exist. The primary products of these reactions, superoxide and hydrogen peroxide, may combine to produce hydroxyl radicals. Of the many potential sources of free radical generation, the enzyme xanthine oxidase has been shown to be important in ischemia in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(47 citation statements)
references
References 43 publications
3
43
0
1
Order By: Relevance
“…In accordance with the results previously re ported by Martz et al (1989), dimethylthiourea (750 mg/kg) significantly reduced the cortical and the to tal infarct volume in this model. The cortical infarct volume was 45.7 ± 16.5 mm 3 in drug-treated rats compared with 79.3 ± 22.6 mm 3 in control rats, and the total infarct volume was 59.5 ± 18.6 mm 3 in drug-treated rats compared with 96.8 ± 29.0 mm 3 in controls (Fig.…”
Section: Focal Ischemia In Ratssupporting
confidence: 92%
“…In accordance with the results previously re ported by Martz et al (1989), dimethylthiourea (750 mg/kg) significantly reduced the cortical and the to tal infarct volume in this model. The cortical infarct volume was 45.7 ± 16.5 mm 3 in drug-treated rats compared with 79.3 ± 22.6 mm 3 in control rats, and the total infarct volume was 59.5 ± 18.6 mm 3 in drug-treated rats compared with 96.8 ± 29.0 mm 3 in controls (Fig.…”
Section: Focal Ischemia In Ratssupporting
confidence: 92%
“…Despite this, studies employing the requisite physiological control and longterm outcome analysis of effects of xanthine oxidase inhibitors on post-ischemic behavior and histology have not been performed. The results from short-term outcome studies in adult rats have been mixed (Lindsay et al, 1991;Martz et al, 1989). More encouraging results have been observed in perinatal brain (Palmer et al, 1993(Palmer et al, , 1990van Bel et al, 1998), but no long-term outcome studies have been reported.…”
Section: Inhibition Of Xanthine Oxidasementioning
confidence: 99%
“…Experiments of the in vivo ESR spectroscopy were conducted with pharmacological interventions; pretreatment with apocynin 31 (Sigma, 5 mg kg À1 , intravenous) 20 mins before in vivo ESR spectroscopy, the use of MC-PROXYL (0.33 mmol per kg body weight) spin probe solution that contained dimethylthiourea 32 (Sigma, 1.0 mmol per kg body weight), or combination of these two interventions. Pretreatment with allopurinol 33 (Sigma, 100 mg kg À1 , intraperitoneal) was also performed 30 min before in vivo ESR spectroscopy.…”
Section: Effect Of Antioxidants On In Vivo Esr Signal Decay Ratementioning
confidence: 99%